Etnobotanical Study on Banana in Karangwangi Village, Cianjur District, West Java - Tatang Suharmana Erawan; Rahmi Aulia Hidayat; Johan Iskandar (Jurnal Biodjati, 2019)
Â Â Banana has been known as one of fruits that has an important function in the rural areas. Bananas have been traditionally planted by rural farmers in the homegarden, garden and mixed-garden in West Java. However, study on bananas in Karangwangi village,Cianjur has not been carried out. Aim of study was to explore varieties (landraces) of bananas, source of local knowledge on bananas, utilization of ba-nanas and diseases of bananas. Method used in this study was quali-tative with ethnobotanical approach and some techniques, including observation and semi-structure interview were applied in this study. The result of study showed that, it was recorded 13 variations of ba-nana; main source of local knowledge on bananas from the parent and friends; utilization of bananas, including consumption of ripe fruit, made of â€œsaleâ€ and some banana organs, including leaves, â€œjantungâ€ (male flower), pseudostem, â€bonggolâ€ (base of pseudostem) and roots of bananas were usually used by people. Main diseases of banana was known by local people as â€œPireusâ€ (virus). We recommended more intensive study on bananas must be carried on for near future.